Needs assessment for a reproductive health registry towards a harmonised reproductive health registry in the occupied Palestinian territory: a qualitative study. (August 2017) - Ghanem, Buthaina; Salman, Rand; Iversen, Bjorn G
Abstract: Background: Reductions of maternal and child mortality are among the UN's Millennium Development Goals. The estimated maternal mortality ratio (MMR) in the occupied Palestinian territory in 2010 was 64 per 100 000 livebirths. WHO has developed a global initiative, the harmonised reproductive health registry (hRHR), to improve data quality and to reduce maternal and infant mortality. We undertook a needs assessment to identify strengths, opportunities, and gaps in the present information system for reproductive health in the occupied Palestinian territory before development of a strategic action plan for the future. Methods: We used a qualitative needs assessment tool (NAT) that has been developed in the International hRHR project and adapted to the Palestinian context. The tool was developed with sections on legal issues, essential indicators, minimum dataset, data collection, data dissemination, and data use. This assessment will help to identify data gaps, which can then be filled to help reduce maternal and child deaths. Through in-depth interviews with senior managers at the Ministry of Health, we adapted the NAT to the Palestinian context. A 1 day workshop with 20 participants from Ministry of Health stakeholder institutions (eg, Department of Primary Health Care) completed the NAT. Findings: The needs assessment showed substantial current data collection in antenatal, perinatal, and postnatal care in local health facilities. However, very little information is exchanged between primary and secondary care, jeopardising the continuum of care and preventing data being used to benefit services provided or for public health purposes. Nationally, reports consist mostly of aggregated, monthly reports of health status and activities that are then published annually. Data are not used for management, to improve quality of care, or to give feedback to health-care providers. Although many of the interventions practised are in line with the essential interventions recommended by WHO, legislation about confidentiality of health data is restricted, and no national agreement has been made about essential interventions, indicators, or a minimum dataset to be collected. Interpretation: Data that are collected should be kept at a necessary minimum and be selected according to evidence-based essential interventions. A way to improve the system would be to introduce a comprehensive computerised hRHR in a consensus-driven process with the major stakeholders in maternal–child health. Funding: WHO Palestinian National Institute of Public Health Project.